Effect of phase-based instruction using geometer's sketchpad on geometric thinking regarding angles - Poh, Geik Tieng; Leong, Kwan Eu (Universiti Putra Malaysia, 2018)
Teaching and learning geometry is not merely about memorising geometrical properties but about grasping the conceptual understanding of geometry as well. Students, however, face challenges in the classroom trying to develop their geometrical thinking. The purpose of this study is to identify whether phase-based instruction using Geometer's Sketchpad helps primary school pupils develop their Van Hiele levels of geometric thinking regarding angles significantly. Eight different pre-sketched activities were designed based on Van Hiele's five phases of learning to guide the students in learning about geometrical angles. Pre and post Van Hiele Achievement Tests were given to both the experimental and control groups before and after the intervention. Inferential statistics such as Mann-Whitney test and Wilcoxon signed-rank test were used in analysing the quantitative data. Results of the pretest indicated no significant difference between both groups of students in their Van Hiele levels of geometric thinking. After the intervention, the findings showed that students in both the experimental and control groups have improved significantly in terms of their Van Hiele levels of geometric thinking. Additionally, results of the Mann-Whitney test revealed that the difference in Van Hiele levels of geometric thinking between students in both groups was significant during posttest. In short, phase-based instruction using Geometer's Sketchpad has helped the students to develop their Van Hiele levels of geometric thinking and provided an insight for the educators to further utilise the software.